Energy issues in the Asia-Pacific region (Institute of Southeast Asian Studies, 2010)
In 2010, we can expect that oil and gas prices will again increase beyond the US$100 per barrel, as the global economy recovers gradually from the global recession and uses more oil and gas.
Keywords: Energy policy--Asia; Power resources--Asia; Energy consumption--Asia; Energy policy--Pacific Area; Power resources--Pacific Area; Energy consumption--Pacific Area